1999
DOI: 10.1021/la9904354
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Acid Neutralization by Overbased Colloidal Additives in Hydrocarbon Media

Abstract: Stopped-flow kinetic studies have been employed to study the mechanism of acid neutralization for the reaction between overbased commercial detergent additives, used as crankcase lubricants, and aqueous strong acids (e.g., HCl and H2SO4) dispersed in the form of water-in-oil microemulsion droplets. Three water-soluble pH indicators, including methyl orange, 4-nitrophenyl-2-sulfonate, and nile blue have been used to monitor the change in pH accompanying the neutralization reaction. This process represents a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 13 publications
4
32
2
Order By: Relevance
“…On the other hand, the surfactant layer should be permeable by the acid molecules produced during the combustion of fuel in order to allow them to reach the carbonate core for neutralization [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the surfactant layer should be permeable by the acid molecules produced during the combustion of fuel in order to allow them to reach the carbonate core for neutralization [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, by inventing a rotating vessel technique Roman [2] reported that in the temperature range of 80-120°C, the higher the temperature, the lower the difference of neutralization ability between lubricants of various compositions. In 2000, by using a stop-flow technique, Hone et al [3] investigated the acid neutralization between microemulsion acid droplets and overbased commercial detergent additives in hydrocarbon media. In the temperature range of 10-30°C, the activation energy for the acid neutralization was relatively low and independent of specific pH indicators being used.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactants act as a dispersed agent, while the metal carbonate acts as a neutralizing agent, and the diluent oil acts as a compatible agent. The term [8][9][10] "over based" demonstrates that the quantity of colloidal metal carbonate in the particle cores is greater than that is needed to neutralize the surfactant acid, otherwise it is described as "neutral" or "low basicity", indicating that the over based detergents have a greater acid neutralizing capacity than their neutral salts. In the present work, different metallic detergent/dispersant additives will be prepared via reaction of dodecyl phenol with calcium hydroxide in different ratios.…”
Section: Introductionmentioning
confidence: 99%